Analysis, design and control of a two stage improved power quality telecommunication power supply. (1st January 2012) - Singh, Shikha; Bhuvaneswari, G.; Singh, Bhim
This paper deals with the power quality improvement at the utility interface of a telecommunication switched mode power supply (SMPS) of 12 kW rating. The first stage of this SMPS consists of a 6-pulse diode bridge converter that performs ac-dc conversion yielding an unregulated dc voltage. In the second stage, two boost rectifiers are connected together which feed to a boost dc-dc full bridge converter connected to the output load. By means of a closed loop control, appropriate value of third harmonic component of the current is injected using a zig-zag transformer to reduce the current harmonics distortion at the utility interface. A detailed design procedure is presented to select various components of the SMPS system.